'Fit and answerable to the degree they hold'?: The gardens of Sir Thomas Temple at Burton Dassett in Warwickshire and Sir Richard Leveson at Trentham Hall in Staffordshire, c. 1630. (1st September 2013) - Francis, Jill
<x xml:space="preserve">Abstract</x> This paper takes as its subject the gardens and gardening activities of the rural county gentry in early seventeenth-century England. Extant gardens from this period are extremely rare and current knowledge is largely limited to the well-documented, but unrepresentative, and extravagant showpieces of the nobility. However, close examination of manuscript collections, household accounts, and contemporary maps, plans and engravings has offered valuable insight into gardens at gentry level, providing new evidence about what was actually happening in the generality of such gardens during the period. Focusing here on the examples of two Midlands gentlemen, Sir Thomas Temple (1567-1636) and Sir Richard Leveson (1598-1661), who were both engaged in creating gardens during the early 1630s at their respective estates in Warwickshire and Staffordshire, it has been possible to add new facets to our fragmentary knowledge of gardens and gardening in the early modern period, as well as to give consideration to the idea that gardens were an appropriate way for a gentleman to demonstrate his standing in society.